Electric Power System Monitoring and Theft Detection using Power Line Communication - Awasthi, Minakshi; Kumar, Amit; Kumar, Deepak; Jeet Pal, Indra (Malikussaleh University, Aceh, Indonesia, 2022)
Electric power theft is a serious concern in the world irrespective of being major revenue losses and developing a nation. More than one-third part of the electricity generated power is lost due to electric theft, power loss, and inefficiencies in the distribution system. Interdicted or illegal utilization of electricity has not only affected economically but also obstructs the design and modeling phases of the power system. Due to electric theft, providing wrong data input values for power system analysis and difficult to load forecasting. In this paper, an inventive Simulink model is designed to detect and monitoring of electric power theft in power system distribution networks through Power Line Communication (PLC). Electric power theft was detected with variance amendment in the amplitude of carrier signal with a narrow band. PLC technique is utilized for data communication over the power line. A narrow band power line carrier signal which has high frequency transferred in power line alongside with power frequency signal. The deviation in the amplitude of the transmitted carrier signal is monitored at the regular time- intervals and the stealing of electricity can be distinguished by the computing of distinction change within the amplitude of the carrier signal. In a normal case, the signal present fixes pattern and waveform, but in the case of power theft, the signal shows some variation and disturbance in a within waveform pattern. A pattern recognition and monitoring approach is used for direct power theft in the PLC model. The Simulink model is performed on MATLAB software to analyze the performance and efficient results that satisfy the proposed Simulink model.